2005
DOI: 10.1530/eje.1.01872
|View full text |Cite
|
Sign up to set email alerts
|

The effects of exercise and adipose tissue lipolysis on plasma adiponectin concentration and adiponectin receptor expression in human skeletal muscle

Abstract: Objective: It has been suggested that adiponectin regulates plasma free fatty acid (FFA) clearance by stimulating FFA uptake and/or oxidation in muscle. We aimed to determine changes in plasma adiponectin concentration and adiponectin receptor 1 and 2 mRNA expression in skeletal muscle during and after prolonged exercise under normal, fasting conditions (high FFA trial; HFA) and following pharmacological inhibition of adipose tissue lipolysis (low FFA trial; LFA). Furthermore, we aimed to detect and locate adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
2
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 63 publications
8
71
2
8
Order By: Relevance
“…Similarly, Kraemer et al (2003) indicated that there was no significant increase in adiponectin levels in young healthy males following a heavy continuous or intermittent running exercise. Finally, Punyadeera et al (2005) reported no significant changes in adiponectin levels during exercise or recovery in healthy normalweight individuals.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, Kraemer et al (2003) indicated that there was no significant increase in adiponectin levels in young healthy males following a heavy continuous or intermittent running exercise. Finally, Punyadeera et al (2005) reported no significant changes in adiponectin levels during exercise or recovery in healthy normalweight individuals.…”
Section: Discussionmentioning
confidence: 90%
“…Research on the effects of acute exercise on adiponectin levels has produced conflicting results. There are studies which have reported no effect of acute exercise on adiponectin levels in healthy, normal weight individuals (Ferguson et al 2004;Kraemer et al 2003;Punyadeera et al 2005). On the other hand, Jurimae et al (2005) reported a significant decrease immediately following exercise and significant increase 30 min post-exercise in healthy normal weight individuals, whereas Kriketos et al (2004) reported that very short exercise training (approximately 1 week) resulted in increased levels of adiponectin and insulin sensitivity in obese individuals without a concomitant body weight loss.…”
Section: Introductionmentioning
confidence: 98%
“…Some of those studies found that the adiponectin level in blood is not affected by acute exercise in healthy, normal weight subjects [15][16][17]. By contrast, adiponectin levels were found significantly decreased immediately after exercise and increased 30 min after exercise in other healthy subjects with normal weight [18].…”
Section: Brief Communication (Original)mentioning
confidence: 99%
“…In most studies, one single exercise could not show acute influence on the plasma adiponectin level, no matter the duration of exercise or whether the subjects are healthy or obese [84,[86][87][88][89]. However, an article published in 2010 reported that both high and low intensity anaerobic exercise could elevate blood adiponectin level in obese men [90], which is similar to the result of another report in 2006 using healthy men with anaerobic exercise [91].…”
Section: Adiponectin In Exercisementioning
confidence: 61%